Model Transshipment Guna Menghasilkan Biaya Pendistribusian yang Minimum Melalui Kajian Teoritis - Ayudina Puji Estrimaz; Mirna Widayanti (Jurnal Teknik Industri, 2002)
PR. KaryaT imur, Malang is an lndustrial Cigarettes which be productive cigarette with Harmonis brand for East Java marketing area, Horizon Super Filter and Horizon Mild Filter for marketing area beyond Java. This research only analized for east java marketing area. This company make use of two (2) source to meet every marketing area needs which is allocated directly through those two source on condition that each sources allocated in accordance with request for every marketing area. It is surely needsa lot of cost, because each sources still had to supply for every marketing area. This research on it's own was submitted to examine a better distribution system so it can minimize cost of distribution.